2009
DOI: 10.1074/jbc.m109.063339
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Galectin-3 with Vascular Cell Adhesion Molecule-1 in Growth Regulation of Mouse BALB/3T3 Cells

Abstract: ␤-Galactose residues on N-glycans have been implicated to be involved in growth regulation of cells. In the present study we compared the galactosylation of cell surface N-glycans of mouse Balb/3T3 cells between 30 and 100% densities and found the ␤-1,4-galactosylation of N-glycans increases predominantly in a 100-kDa protein band on lectin blot analysis in combination with digestions by diplococcal ␤-galactosidase and N-glycanase. When cells at 100% density were treated with jack bean ␤-galactosidase, the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Another possible candidate is VCAM‐1, as removal of sialic acid increases leukocyte trafficking, but this phenomenon was difficult to explain, as no N ‐glycan sites are found in proximity to the VLA‐4 binding domain . This gap has recently been clarified by studies demonstrating that galectin‐3 can bind to VCAM‐1 and support leukocyte adhesion . With PECAM‐1, α‐2,6‐sialic acid has been reported to be critical for homodimerization and associated antiapoptotic signaling .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible candidate is VCAM‐1, as removal of sialic acid increases leukocyte trafficking, but this phenomenon was difficult to explain, as no N ‐glycan sites are found in proximity to the VLA‐4 binding domain . This gap has recently been clarified by studies demonstrating that galectin‐3 can bind to VCAM‐1 and support leukocyte adhesion . With PECAM‐1, α‐2,6‐sialic acid has been reported to be critical for homodimerization and associated antiapoptotic signaling .…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that innate differences in surface carbohydrate patterns exists across vascular endothelium in vivo which is further modified during inflammation and disease . Moreover, it is now evident that endothelial cell expressed carbohydrates are involved in leukocyte trafficking, with these sugars providing a “zip code” to allow specific leukocyte subsets to migrate into specific tissues in response to specific stimuli . For example, our recent studies demonstrate a role for endothelial high mannose N ‐glycans in monocyte rolling/adhesion and suggest that N ‐glycosylation per se is regulated by inflammatory stimuli, by mechanisms that are distinct from those that affect adhesion molecule protein expression .…”
Section: Introductionmentioning
confidence: 98%
“…3). It has been reported that recombinant galectin 3 columns bind several proteins from BALB=3T3 cells, and the major band, at 100 kD, was identified as VCAM-1 by mass spectrometry (278). Moreover, VCAM-1 is immunoprecipitated from proteins bound to a recombinant galectin-3 column (278).…”
Section: B Ligands and Vcam-1 Binding Regionsmentioning
confidence: 99%
“…Expression and secretion of Gal-3 has been well documented in NFs [46][47][48][49][50] and its silencing at the genetic level led to inhibition of fibroblast proliferation [51]. Similarly, Gal-3 knockout in mouse embryonic fibroblasts (MEFs) or Gal-3-depletion in human skin NFs decreased cell proliferation and increased premature senescence, highlighting a role for Gal-3 in senescence regulation [52].…”
Section: Galectin-3 In Fibroblastsmentioning
confidence: 99%